Revitalization Of Local Government Internal Oversight Through The Inspectorate In Tegal Regency - Pertiwi, Nandhea Fani Dian Pertiwi (International Journal of Educational Research & Social Sciences, 2023)
The government apparatus has the main task of carrying out the general duties of government and development tasks. Supervision is a management function to control the course of the organization so that the goals are effective, efficient and economical in accordance with applicable laws and regulations. With supervision, the input can be obtained for decision makers to stop or eliminate errors, irregularities, misappropriation, waste, prevent recurrence to achieve goals in carrying out the main tasks and functions of the organization and achievement of the vision and mission of the organization so that the goals are effective, efficient and economical in accordance with applicable laws and regulations. So based on this, the formulation of the problem in this study is 1) what is the benchmark for the performance of a government in an effort to realize good government?; 2) What is the supervisory function of the inspectorate in realizing clean local government?; 3) How are the efforts to revitalize the internal supervision of local governments through the Inspectorate in Tegal Regency? The author uses the normative juridical approach Method The normative juridical approach method uses secondary data. Data analysis using descriptive qualitative. The data collection methods used by the authors include literature studies. The results of the study found that The assessment of the good and bad of government can be assessed if it has intersected with elements of the principles of good governance. The principles of good governance include community participation, the establishment of the rule of law, transparency built on the basis of the free flow of information, caring for stakeholders, oriented towards consensus, equality, effectiveness, accountability, and vision. Supervisory function To realize an optimal supervision system, a structured and integrated approach must be established starting from the planning, implementation, reporting and follow-up stages of supervision results by all interested parties and work units.Supervision of the implementation of local government is a process of activities aimed at ensuring that local governments are in accordance with the plans and provisions of applicable laws and regulations.Efforts to Revitalize Internal Supervision of Local Government through the Inspectorate in Tegal Regency are by realizing good governance and the realization of good governance indicators, namely accountability, transparency and certainty.